Race, color, identity : rethinking discourses about 'Jews' in the twenty-first century - Sicher, Efraim (Berghahn Books, 2013)
Advances in genetics are renewing controversies over inherited characteristics, and the discourse around science and technological innovations has taken on racial overtones, such as attributing inherited physiological traits to certain ethnic groups or using DNA testing to determine biological links with ethnic ancestry. This book contributes to the discussion by opening up previously locked concepts of the relation between the terms color, race, and "Jews", and by engaging with globalism, multiculturalism, hybridity, and diaspora. The contributors-leading scholars in anthropology, sociolog.